Generalidades del sistema de la seguridad social integral y el nuevo mecanismo de pago planilla integral de la liquidación de aportes (2010)
Social security is a fundamental right under the national constitution and guarantor of this protection is the state, who must ensure that all Colombians to enjoy this protection Colombian Social Security came to take their first steps in 1946, when you create the Colombian Institute of Social Security through Law 90 of December 26 1946.Quienes take the date of December 26, 1946 as the origin, do business under the strong argument has been given to the legal life of the old Colombian Social Security Institute, an organization that protected first pension insurance in the ways of old age, disability, death, sickness, maternity, occupational accidents and diseases professionals. It is noteworthy that the pension program only began in the year 1967 from the month of January - when I go into force of the 3041 Decree was issued in 1966.